2018
DOI: 10.1111/jch.13371
|View full text |Cite
|
Sign up to set email alerts
|

Unobserved automated office BP is similar to other clinic BP measurements: A prospective randomized study

Abstract: Results of the SPRINT study have been disputed, based on the assumption that unattended BP measurements do not correlate with usual BP measurements. In this study, the authors investigated the correlation of unattended SPRINT‐like measurements with other conventional measurements. All BP measurements were taken with the patient seated in a comfortable chair with the legs uncrossed and not speaking during the procedure. For the purpose of this study, sixty‐five patients, mostly male (93%), were recruited from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Their study, performed in a specialized hypertension center, found unattended systolic office BP not only to be lower than conventional manual office BP readings but also 6 mm Hg lower than home BP . Similarly, Papademetriou et al investigated the correlation of unattended SPRINT‐like measurements with other conventional BP measurements and concluded that all BP measurements were similar with no statistically significant difference . On the other hand, a cross‐sectional study of 158 patients conducted in the offices of four general practitioners compared conventional auscultatory office BP and unattended AOBP measurements in 107 subjects, and unattended and attended AOBP in another 51 subjects .…”
Section: The Clinical Value Of Aobpmentioning
confidence: 99%
“…Their study, performed in a specialized hypertension center, found unattended systolic office BP not only to be lower than conventional manual office BP readings but also 6 mm Hg lower than home BP . Similarly, Papademetriou et al investigated the correlation of unattended SPRINT‐like measurements with other conventional BP measurements and concluded that all BP measurements were similar with no statistically significant difference . On the other hand, a cross‐sectional study of 158 patients conducted in the offices of four general practitioners compared conventional auscultatory office BP and unattended AOBP measurements in 107 subjects, and unattended and attended AOBP in another 51 subjects .…”
Section: The Clinical Value Of Aobpmentioning
confidence: 99%
“…Available fully automated devices are listed at http://www.dableducational.org/ and in the British and Irish Hypertension Society (https://bihsoc.org/bpmonitors/) (ie, BpTRU, Microlife WatchBP Office, Omron HEM 907, Omron HEM 705CP) . Other BP devices that have been used to perform automated measurements in published studies are the following: the BP monitor CB‐1805‐B Biox the Dinamap pro‐Care the Omron M10IT the Task Force Monitor CNS (this monitor performs beat‐to‐beat BP monitoring but it has also been used to perform automated measurements) the Omron 9000Ai, and the Omron HEM 7080 IC …”
Section: Factors That Influence Aobp Measurements Are the Followingmentioning
confidence: 99%
“…Its results revealed that, at the first office visit, the difference in systolic BP values between AOBP and awake ABP was smaller compared with the systolic BP values between auscultatory office and the mean awake ABP by 2.3 mm Hg and 6.5 mm Hg, for AOBP and auscultatory technique, respectively . Meanwhile when conventional clinic measurements, using oscillometric or auscultatory technique, were taken carefully following a standardized BP measurement procedure, similar BP values were recorded . Moreover, it has been shown that the unattended AOBP readings have a stronger association with subclinical CV disease and organ damage, including left ventricular hypertrophy .…”
Section: Introductionmentioning
confidence: 99%
“…Four studies have specifically addressed the impact of the presence of an observer on OBP by using the SPRINT study measurement protocol. [10][11][12][13] Three of these studies showed minor differences in the range of <3 mm Hg, [10][11][12] and only one showed attended systolic OBP to be higher by 8.6 mm Hg. 13 In conclusion, we fully agree with Martin Myers that for the accurate diagnosis and optimal management of hypertension OBP must be carefully standardized and complemented by out-of-office BP measurement.…”
mentioning
confidence: 93%